Paraoxonase 2 Deficiency Causes Mitochondrial Dysfunction in Retinal Pigment Epithelial Cells and Retinal Degeneration in Mice - Parameswaran Gangadharan Sreekumar; Feng Su; Christine Spee; Elise Hong; Ravikiran Komirisetty; Eduardo Araujo; Steven Nusinowitz; Srinivasa T. Reddy; Ram Kannan (MDPI AG, 2023)
Although AMD is a complex disease, oxidative stress is a crucial contributor to its development, especially in view of the higher oxygen demand of the retina. Paraoxonase 2 (PON2) is a ubiquitously and constitutively expressed antioxidant protein that is found intracellularly associated with mitochondrial membranes and modulates mitochondrial ROS production and function. The contribution of PON2 to AMD has not been studied to date. In this study, we examined the role of PON2 in AMD utilizing both in vitro and in vivo models of AMD with emphasis on mitochondrial function. Mitochondrial localization and regulation of PON2 following oxidative stress were determined in human primary cultured retinal pigment epithelium (hRPE) cells. PON2 was knocked down in RPE cells using siRNA and mitochondrial bioenergetics were measured. To investigate the function of PON2 in the retina, WT and PON2-deficient mice were administered NaIO3 (20 mg/kg) intravenously; fundus imaging, optical coherence tomography (OCT), electroretinography (ERG) were conducted; and retinal thickness and cell death were measured and quantified. In hRPE, mitochondrial localization of PON2 increased markedly with stress. Moreover, a time-dependent regulation of PON2 was observed following oxidative stress, with an initial significant increase in expression followed by a significant decrease. Mitochondrial bioenergetic parameters (basal respiration, ATP production, spare respiratory capacity, and maximal respiration) showed a significant decrease with oxidative stress, which was further exacerbated in the absence of PON2. NaIO3 treatment caused significant retinal degeneration, retinal thinning, and reduced rod and cone function in PON2-deficient mice when compared to WT mice. The apoptotic cells and active caspase 3 significantly increased in PON2-deficient mice treated with NaIO3, when compared to WT mice. Our investigation demonstrates that deficiency of PON2 results in RPE mitochondrial dysfunction and a decline in retinal function. These findings imply that PON2 may have a beneficial role in retinal pathophysiology and is worthy of further investigation.